2021
DOI: 10.3389/fped.2021.745444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality of Life of 231 Children With Primary Nephrotic Syndrome and Assessing Parental Awareness of the Disease

Abstract: Objective: This study aims to investigate the quality of life of children with primary nephrotic syndrome (PNS), assess their parents' disease awareness, and provide a basis for the comprehensive management of children with PNS.Methods: A total of 231 children with PNS who were hospitalized in the Department of Pediatric Renal Rheumatology and Immunology in the ShengJing Hospital of the China Medical University from March 2019 to October 2020 were selected as the study subjects. The subjects and their parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The school functioning of the patients was the lowest which is coherent with the outcomes of Selewski et al . [ 5 ] and a recent study of 231 Chinese children with NS [ 19 ] and a recent report from India [ 20 ]. All school children with NS in this study missed school to go to the hospital or because not feeling good however, most of them did not show difficulties in class and did not have trouble with homework.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The school functioning of the patients was the lowest which is coherent with the outcomes of Selewski et al . [ 5 ] and a recent study of 231 Chinese children with NS [ 19 ] and a recent report from India [ 20 ]. All school children with NS in this study missed school to go to the hospital or because not feeling good however, most of them did not show difficulties in class and did not have trouble with homework.…”
Section: Discussionmentioning
confidence: 99%
“…The physical functioning of our studied group was considerably lower than controls. Li et al ; reported that most of the children in their report faced a negative impact of NS on physical activity [ 19 ]. In a former study of children with SLE, Moorthy et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the average age of onset of NS at 3 years, however, many children could endure a decade or more of relapsing disease with repeated exposure to corticosteroids, steroidsparing therapeutics, and their associated side effects. This ultimately leads to a significant health care burden and reduced quality of life and children would benefit from induction of long-term remission early in the disease course [2,8].…”
Section: Introductionmentioning
confidence: 99%